Peran Mediasi Kompetensi Pada Pengaruh Rekrutmen, Seleksi Dan Training Terhadap Kinerja Karyawan Toko Lab Art Aromatique Cabang Jawa Timur - Syaifullah, Ahmad; Sutapa, Heru (Universitas Maritim AMNI Semarang, 2023)
The role of human resources is needed to achieve good results within the company. Whether a company develops or not depends on the human resources in the company itself. Companies are required to find and print employees who will later provide good work results. Performance can be influenced by recruitment, selection and training and can be through the role of competency variables. The study aims to determine the role of recruitment, selection, and training on employee performance with competence as a mediating variable at the Aromatique Art Lab Store East Java Branch. The subject of the study was an employee of the East Java Branch of the Aromatique Art Lab Store. The employee sample consisted of 44 employees. The sampling technique is non probability sampling. The study used the Smart-PLS method. The results show that: (1) Recruitment does not have a significant effect on Employee Performance. (2) Selection does not significantly affect Employee Performance. (3) Training has a significant effect on Employee Performance. (4) Recruitment does not significantly affect the Competency to the extent. (5) Selection does not significantly affect the Competence. (6) Training has a significant effect on competence. (7) Competency has a significant effect on Employee Performance. (8) Recruitment has no significant effect on Competency-mediated Employee Performance. (9) Selection has no significant effect on Competency-mediated Employee Performance. (10) Training does not significantly affect Competency-mediated Employee Performance. The benefits of research are as material for taking company policies in encouraging employee performance and as a reference for further researchers. The next suggestion of researchers is that they are expected to look at other variables outside the variables used in this study in order to get maximum results.